Tindak Pidana Penipuan dengan Menggunakan Sarana Akta Perjanjian yang Dibuat di Hadapan Notaris - Helmi Abdul Azis; Dahlan Ali; Suhaimi (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
Notarial deed as an authentic deed has an important function in the life of society. The need for authentication in writing, in the form of an authentic deed is increasing in line with the growing demand for legal certainty which is one of the principles of the state of law. Notarial deed is the perfect tool of verification so as to ensure legal certainty, but in recent times it often used as a tool to commit crimes of fraud or other crimes. The results show that the deed of agreementmade in front of the notary can serve as a means to commit fraud criminal acts. For example, a deed made without the presence of complete parties, unclear object of the agreement and contains an unlawful causa element in the agreement which would potentially cause harm to either party in terms of misusing of the deed. The use of notarial deed as a tool for committing fraud crimes is a development of the modus operandi of crime by taking refuge behind thesanctity of the agreement, meaning that it is nothing other than to be protected from criminal penalties. A notary may be held accountable for crimes of fraud committed by another person by using the deed of agreement made in front of him as a tool of fraud crime. Certainly, with a note that a notary has issued a deed which he knows contains legal defects and then the deed is used by others as a tool of fraud crime, the act is included in the qualification of crime aids(medeplichtigheid).